How an unequal intra-firm resources distribution affect market share - Davcik, N.; Grigoriou, N (Marketing Intelligence and Planning, 2020)
Purpose: The study addresses how marketing assets and resources of the firm perform under different product (brand) innovation conditions using the dynamic marketing capabilities (DMC) research perspective. The study contributes to the DMC research stream showing the effects and performance of heterogeneous firm drivers and resources. Academic research to date has paid a little attention to the interrelationship between market share as a performance metric, dynamic capabilities, and product (brand) innovation. The current study bridges this knowledge gap by empirically validating the effects of DMC on market share performance output using panel data of retail food brands. Methodology: The model was initially fitted with the beta regression analysis and cluster analysis in the second step of the estimation procedure. The results of simulation by Monte Carlo experimentation are discussed. Findings: The findings show that firms leverage their marketing capabilities unequally in the multi-brand portfolios, which leads to an unequal intra-firm distribution of assets and resources. The research contributes to the understanding of the brand competitive dynamics and appropriate deployment of assets and resources for improved firm performance. Originality: These findings are useful for both academics and practitioners because they address new and future research. In doing so, we advance the firm performance and branding literature with extension in the DMC literature.